The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1016/0014-5793(93)81591-m
|View full text |Cite
|
Sign up to set email alerts
|

Relative stability of AT and GC pairs in parallel DNA duplex formed by a natural sequence

Abstract: The low-cooperative melting of parallel DNA formed by a natural 40 bp long sequence from Drosophila:that possesses a normal nucleotide content was studied by using the special method of measuring the fluorescence of its complex with acriflavine as well as by conventional thermal denaturation. Acriflavine allows discrimination of the melting of AT and GC pairs because its fluorescence is quenched by neighbouring G bases. We have observed that about 40% of AT pairs melt at 14°C while the remainder melt at 42°C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…There are few reports of parallel stretches in native DNA because every system in vivo uses the Watson-Crick-type anti-parallel duplex between complementary strands. Tchurikov and co-workers reported parallel duplex formation for specific functions in local regions of DNA (10)(11)(12). Such a parallel duplex has been also detected in Escherichia coli mRNA (13).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…There are few reports of parallel stretches in native DNA because every system in vivo uses the Watson-Crick-type anti-parallel duplex between complementary strands. Tchurikov and co-workers reported parallel duplex formation for specific functions in local regions of DNA (10)(11)(12). Such a parallel duplex has been also detected in Escherichia coli mRNA (13).…”
Section: Introductionmentioning
confidence: 82%
“…Observations indicating the formation of a unique structure were done by comparison of CD spectra recorded during the temperature-driven association (85°C/15°C) of the [R P -PS]-dA 12 Fig. 2S, respectively) changed from high temperature spectra characteristic for single strands (a broad positive band of low intensity centered at 272 nm, crossover points at 260 and 290 nm) to low temperature spectra typical for an A-form helix (a broad positive band of high intensity centered at 268 nm, crossover points at 254 and 295 nm).…”
Section: Studies By CD Spectroscopymentioning
confidence: 99%
“…Typically, any time that linear probes are used for detection, there is a risk that false annealing may occur. Probetarget hybridization is highly temperature dependent, and depending on the nucleotide composition of the probe, random annealing can pose a problem, especially when one is dealing with sequences with high GϩC contents, since the temperature profile for annealing is shifted downward (5,38).…”
Section: Discussionmentioning
confidence: 99%
“…In 1992, Tchurikov et al showed that parallel complementary probes of normal nucleotide consisting of both AT/GC base pairs can be used for molecular hybridization experiments, indicating the stability of G-C containing parallel DNA (5). In 1993, Borisova et al reported that G-C pairs in a 40 base pair parallel duplex DNA (consisting of natural DNA sequence) are more thermostable than A-T base pairs (6). Furthermore, other similar reports have shown that there are no drastic differences in nearest neighbor base pair interactions between PS-DNA and APS-DNA having mixed AT/GC composition (7).…”
Section: Introductionmentioning
confidence: 99%